2014
DOI: 10.1002/ejoc.201403441
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Catalytic Activity of BINOL‐Derived Silanediols

Abstract: Enantiopure silanediols derived from BINOL are an innovative family of stereoselective hydrogen‐bond donor (HBD) catalysts. Silanediols incorporated into a BINOL framework are attractive catalysts, as they are readily accessible and highly customizable. Structural modifications of the BINOL backbone affect the reactivity and selectivity of the silanediol catalysts in the additions of silyl ketene acetals to N‐acyl isoquinolinium ions. The best results were obtained when the silanediol scaffold was substituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…A subsequent paper showed that substitution of the BINOL scaffold in 108 with phenyl rings could improve the yield and enantioselectivities of the reaction. 122 Mattson also showed that these chiral silanediols could hydrogen bond to the triflate anion with surprisingly high affinities for what is typically considered 123 a noncoordinating anion (Ka ~ 2300 M -1 in CHCl3). 124 Binding to chiral silanediols (e.g.…”
Section: Catalysis and Reactivitymentioning
confidence: 98%
“…A subsequent paper showed that substitution of the BINOL scaffold in 108 with phenyl rings could improve the yield and enantioselectivities of the reaction. 122 Mattson also showed that these chiral silanediols could hydrogen bond to the triflate anion with surprisingly high affinities for what is typically considered 123 a noncoordinating anion (Ka ~ 2300 M -1 in CHCl3). 124 Binding to chiral silanediols (e.g.…”
Section: Catalysis and Reactivitymentioning
confidence: 98%
“…1-Methoxy-1-(triethylsiloxy)-2-methyl-1-propene ( Et3 SKA) was synthesized via the reaction of methyl isobutyrate and chlorotriethylsilane, in accordance with a method reported in the literature. 18 Methyl isobutyrate (14.0 g, 137 mmol) in THF solution (200 mL) was charged into a flask filled with dry nitrogen gas, following which 1.5 M lithium(diisopropylamide) (100 mL, 150 mmol) in THF was added dropwise with vigorous stirring at −78°C for 30 min. Subsequently, N,N'-dimethylpropyleneurea (200 mmol) and chlorotriethylsilane (22.6 g, 150 mmol) in THF solution (50 mL) were added, and the reagents were stirred at −78°C for 60 min, following which they were warmed to room temperature.…”
Section: Synthesis Of Silyl Ketene Acetal (Ska)mentioning
confidence: 99%
“…1, Scheme 1). While these new catalysts have been proven to be potent HBD catalysts, the syntheses are challenging [47]. Compared to these stable carbon-connected silanediols, the readily accessible alkoxy silanediols undergo fast condensation reactions which often lead to unknown and insoluble polysiloxanes [5051].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen-bonding silanediols, i.e., di(1-naphthyl)silanediol ( 1 ) [39], silanediols 2 [4143], binaphthylsilanediol derivatives 3 [4546] and 4 [4748] and novel biphenyl-2,2’-bisfenchyloxydichlorosilane ( 7 ), biphenyl-2,2’-bisfenchyloxychlorohydroxysilane ( 8 ) and biphenyl-2,2’-bisfenchyloxysilanediol ( 9 ) with precursor BIFOL ( 5 ) [52] and phosphite derivative BIFOP-Cl ( 6 ) [53]. …”
Section: Introductionmentioning
confidence: 99%